The Vicissitudes of a Failed visit: Enrico Ferriand the National University of Cordoba at the Beginning of the 20th Century - Portelli, María Belén (CIAN-Revista de Historia de las Universidades, 2018)
The purpose of this article is to analyze the conflictive circumstances that took place in the National University of Cordoba (Argentina) around the potential visit of the italian socialist and criminologist Enrico Ferri in 1910. The episode allows us to perceive a set of actors; ideas and representations in force at that time. Consequently; it contributes to advance in the understanding of the cultural transformations that developed at the university during the transition from the 19th century to the 20th century.
Keywords: Argentina; National University of Cordoba; Enrico Ferri; cultural visits; law